The Effect of Autistic Traits on Social Orienting in Typically Developing Individuals - Lin, Guoyao; Cui, Yanling; Zeng, Jiajing; Huang, Liang (Frontiers in Psychology, 2020)
Autism spectrum disorder is a complex neurodevelopmental disorder characterized by wide ranging and heterogeneous changes in social and cognitive abilities, including deficits in orienting attention during early processing of stimuli. Investigators have found that there is a continuum of autism-like traits in the general population, suggesting that these autistic traits may be examined in the absence of clinically diagnosed autism. To provide evidence for the continuum of autistic traits in terms of social attention and to provide insights into social attention deficits in people with autism, the current study was conducted to examine the effect of autistic traits of typically developing individuals on social orienting using a spatial cueing paradigm. The typically developing individuals who participated in this study were divided into hight autistic traits and low autistic traits groups using the Autism Quotient scale. All participants completed a spatial cueing task in which social cues (gaze) and nonsocial cues (arrow) were presented under different cue predictability conditions (predictive vs. nonpredictive) with different SOAs (100 ms vs. 400 ms). The results showed that compared to low autistic individuals, high autistic individuals had less benefit from nonpredictive social cues but greater benefit from nonsocial ones, providing evidence that such spatial attention impairment in high autistic individuals is specific to the social domain. Interestingly, the smaller benefit from nonpredictive social cues in high autistic individuals was shown only in the 400 ms condition, not in the 100 ms condition, suggesting that their difficulties in orienting to nonpredictive social cues may be caused by a deficiency in spontaneously effortful control processing.